A PROSPECTIVE CONSIDERATIONS AND COMPARATIVE EFFICACY BETWEEN IVABRADINE VS BETA BLOCKERS IN SOUTH INDIAN ACUTE CORONARY SYNDROME PATIENTS - BATTULA, PRADEEP; REDDY B, PRATHIMA; L, POONAM; KUMAR L, HEMANTH; SRI N, DIMPU (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: the objective of this study was to assess the role of heart rate in acute coronary syndrome with reduced ejection fraction, to assess contraindications for beta blockers, to assess the tolerability between Ivabradine and Beta-Blockers, to assess efficacy between Ivabradine and Beta Blockers, to assess patient condition according to NYHA classification. Methods: A Prospective observational study was conducted for a duration of6 months Study population includes 100 patients in which Group A-50, Group B-50. We were selected the subjects according to inclusion and exclusion criteria. The patients were classified in one of four categories based on their symptoms in regards to normal breathing and varying degrees in shortness of breath by using (The New York Heart Association) NYHA Classification. Results: Majority of the patients were in age group between (55-64)(32%) years of age are highly affected with ACS. Prevalence of ACS is high in Rural (56%). Both drugs decreased the mean heart rate to 89.97±10.27 (Group-A) versus 86.76±13.14 (Group-B) beats per minute (P=0.24). The result obtained are clinically and statistically significant with statistical significance at P>0.05. Conclusion: In the present study we considered and compared the efficacy between Ivabradine and Beta Blockers in south Indian acute coronary syndrome patients shows Ivabradine is as effective as betablockers in reduction of heart rate.